Factors associated with differences in vitamin D levels between the urban and rural population of Malaysia / Nurbazlin Musa - Nurbazlin , Musa (2016)
Background: UV-B sunlight exposure is a primary source of vitamin D. There have been reports of low vitamin D status amongst the Malaysian population despite it being a tropical country. This study was conducted to determine the vitamin D status in urban and rural women in Malaysia and factors predicting 25(OH)D levels. Methods: Serum 25(OH)D was measured along with demographic and physical characteristics, intact parathyroid hormone (i-PTH), sun exposure and dietary vitamin D and calcium intake in urban and rural women aged above 45 years. Results: Median (Q25-Q75) age of the subjects was 57 (53-61) years. Rural women had significantly higher median (Q25-Q75) levels of 25(OH)D compared to urban women [69.50 (58.95-79.14) vs 31.90 (26.05-45.50) nmol/L, p<0.001]. Majority of urban women (43.9%) had vitamin D deficiency (<30 nmol/L), while most of rural women (88.1%) were vitamin D sufficient (≥50 nmol/L). Although rural women had significantly lower fraction of body surface area (BSA) exposed to sunlight compared to urban women [0.12 (0.07-0.17) vs 0.21 (0.21-0.43), p<0.001], but they spent a lot of time in the sun compared to urban women [7.83 (3.67-14.71) vs 2.92 (1.17-4.92) hours, p<0.001], leading to significantly higher calculated sun index (hours of sun exposure per weekfraction of BSA) compared to urban women [0.89 (0.42-1.83) vs 0.72 (0.26-1.28), p=0.018]. Median (Q25-Q75) vitamin D intake of rural women was higher compared to urban women [5.23 (3.31-8.45) vs 4.61 (2.66-7.41) μg/day, p=0.050]. Rural women also had significantly higher median (Q25-Q75) intake of calcium compared to urban women [529.84 (328.17-736.09) vs 423.49 (324.28-561.67) mg/day, p=0.001] respectively. Only 7.5% of urban women and 19.1% of rural women met the iv recommended nutrient intake (RNI) for vitamin D. A total of 8.9% of rural women met the RNI for calcium compared to 0.9% of urban women. Significantly positive correlation were found between waist circumference (rho=0.114, p=0.023), darkest (rho=0.137, p=0.006) and delta (rho=0.115, p=0.022) skin colour score, hours of sun exposure per week (rho=0.342, p<0.001), sun index (rho=0.180, p<0.001) and dietary calcium intake (rho=0.162, p=0.001) with serum 25(OH)D levels. Conversely, age (rho=-0.028, p<0.001), household income (rho=-0.224, p<0.001) and fraction of BSA exposed to sunlight (rho=-0.264, p<0.001) were negatively correlated with serum 25(OH)D levels. However, there were no significant correlation between BMI (p=0.248), body fat percentage (p=0.061), lightest skin colour score (p=0.212), serum i-PTH (p=0.342) and dietary vitamin D intake (p=0.095) with serum 25(OH)D levels. In the stepwise linear regression, rural dwelling, being Chinese and use of vitamin D containing supplements increased the serum 25(OH)D by 37.09, 9.72 and 6.11 nmol/L respectively. Moreover, 25(OH)D levels increased by 0.29 nmol/L for every unit increment in hours of sun exposure per week. Conclusion: Rural women in Malaysia had significantly higher vitamin D levels compared to urban women. Higher sun exposure and better dietary intake of vitamin D and calcium may have contributed to the differences in vitamin D status. Rural dwelling, being Chinese, hours of sun exposure per week and use of vitamin D containing supplements were key factors influencing vitamin D status in Malaysian women.